Fractional-order integral resonant control of collocated smart structures. (November 2016) - Feliu-Talegon, D.; San-Millan, A.; Feliu-Batlle, V.
Abstract: This paper proposes a fractional-order integral controller, FI, which is a simple, robust and well-performing technique for vibration control in smart structures with collocated sensors and actuators. This new methodology is compared with the most relevant controllers for smart structures. It is demonstrated that the proposed controller improves the robustness of the closed-loop system to changes in the mass of the payload at the tip. The previous controllers are robust in the sense of being insensitive to spillover and maintaining the closed-loop stability when changes occur in the plant parameters. However, the phase margin of such closed-loop systems (and, therefore, their damping) may change significantly as a result of these parameter variations. In this paper the possibility of increasing the phase margin robustness by using a fractional-order controller with a very simple structure is explored. This controller has been applied to an experimental smart structure, and simulations and experiments have shown the improvement attained with this new technique in the removal of the vibration in the structure when the mass of the payload at the tip changes. Abstract : Highlights: A fractional order controller was designed robust to spillover. It also presented a phase margin robust to large parametric variations. Simulated and experimental responses were obtained. Our controller showed superior performance and robustness than others.